Penerapan Media Pembelajaran Canva Ai Pada Mata Pelajaran Informatika Kelas X Di Sma Negeri 3 Gorontalo Utara - Puluhulawa, Alda Cahyani; Hadjaratie, Lillyan; Suhada, Sitti; Koniyo, Moh. Hidayat; Kadim, Ahmad Azhar; Bouty, Abd. Aziz (Universitas Lampung, 2024)
This research aims to develop learning media using Canva as a tool to help students improve their learning outcomes in the subject of Algorithms and Programming by creating Canva AI learning media that contains content capable of visualizing the material. The method used in this research is the Research and Development development method with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The results of the feasibility test by content experts showed a feasibility score of 4.6 with the category